Charge Accumulation Model Under The Influence Of Light - Akimenko T.A., Larkin E.V., Ostashev S.V., Kuznetsova T.R. (International Journal of Advanced Science and Technology, 2020)
The features of the functioning of CCD-type sensors have been investigated, it has been shown that a CCD-type sensor is most suitable for registering fast-moving markers. It is shown that from the values of the pixels formed in the color planes, a color space can be formed, the coordinates of which are codes of radiation intensities in the red, green and blue regions of the spectrum. To describe the process of charge accumulation in CCD, the concept of an actualizing light flux is introduced, which causes the generation of a given number of electron-hole pairs in the photosensitive element of the photoelectronic converter. A model of charge accumulation in the photosensitive element of the photoelectronic converter is constructed, based on the consideration of physical processes, the formation of electron-hole pairs and the formation of space charges